Isolation and identification of pathogenic leptospira spp from environmental samples during and after 2017 flood in Kelantan - Katman, Mohammad Salihen (Universiti Sains Malaysia, 2017)
Leptospirosis is a zoonosis found worldwide, the main reservoir is the rat. Human infection generally results from exposure to contaminated river or lake or animals. The outbreak of leptospirosis around the world has been associated with heavy rainfall and flooding. These extreme weather events increase the risk of leptospirosis to those who live within Leptospira-contaminated environments and also the magnitude of outbreaks. The study aimed to isolate and identify the presence of pathogenic Leptospira spp in an environmental sample during the flood (52 samples) and after the flood (52 samples) from three districts which were Tumpat, Pasir Mas and Kota Bharu. The sample was cultured and enriched in liquid EMJH, a selective media for Leptospira followed by dark-field microscope (DFM) observation to determine the positive morphology of Leptospira. PCR targeting LipL32 were performed, which is present only in pathogenic Leptospira spp. Findings revealed 35 positive samples (67 %) during the flood for Leptospira under DFM: 19 from Tumpat, 10 from Pasir Mas and 6 from Kota Bharu. Four samples: 3 from Tumpat and 1 from Pasir Mas were detected as pathogenic Leptospira. Meanwhile, an amount of 32 samples (62 %) after the flood was found as positive for Leptospira under DFM: 15 from Tumpat, 6 from Pasir Mas and 11 from Kota Bharu. Eighth samples: 4 from Tumpat, 3 from Pasir Mas and 1 from Kota Bharu were detected as pathogenic Leptospira. Therefore, this study successfully isolated and identified pathogenic Leptospira spp in environmental samples affected by flood.